Piezomagnetic and ultrasonic properties of the Fe-Cu-Nb-Si-B metallic glass after heat-treatment - KACZKOWSKI, Z.; MAŁKIŃSKI, L.; MÜLLER, M. (Archives of Acoustics, 1993)
An Fe73.5Cu1Nb3Si16·5B6 alloy was cast as an initially amorphous ribbon. The samples about 50-51 mm long and 4 mm wide were cut out from the 10mm wide and about 15μm thick ribbon and annealed at the temperatures over 300°C (to 550°C) in the transverse magnetic field H_⊥ and also without magnetic field (H =0). Before nanocrystallization this alloy exhibits the saturation magnetostriction equal to (20-23)x10^-6. The annealing at the temperatures over 400°C in the transverse magnetic field increases the maximum value of the magnetomechanical coupling coefficient (k_m) from 0.10-0.15 (for as quenched state) to over 0.45. The magnetic anisotropy, introduced during the heat-treatment in the transverse magnetic field, is responsible for the predominant vector rotation mechanism which increases the magnetomechanical coupling and ΔE-effect.